Building a House in Heaven : Pious Neoliberalism and Islamic Charity in Egypt - Atia, Mona (Book collections on Project MUSE., 2013)
In this book, the author makes the connection between Islam and capitalism to examine the surprising relations between charity and the economy, the state, and religion in the transition from Mubarak-era Egypt. She draws on interviews with key players, exploring the geography of Islamic charities through multiple neighborhoods, ideologies, sources of funding, projects, and wide social networks. -- Provided by publisher.